2012
DOI: 10.2478/v10184-010-0028-z
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and seed traits of Berberis croatica Horvat and Berberis vulgaris L.

Abstract: -The three year variability of fruits and seeds was investigated inThe fruit shape of both species was similar and the length/width ratio was 1.91-2.04 in B. croatica and 1.77-2.07 in B. vulgaris. The number of seeds per fruit was 1.23-1.58 in B. croatica and 1.36-1.54 in B. vulgaris. Generally, fruits and seeds of B. vulgaris were significantly longer, wider and heavier than fruits and seeds of B. croatica. ANOVA showed significant statistical differences between populations for all analyzed fruit and seed tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…Both fruits are similar in appearance and shape. It was determined that the pomological values obtained here are quite similar to the values reported in the literature (Kremer, Grubesic, Popovic, & Karlovic, 2012).…”
Section: Pomological Resultssupporting
confidence: 89%
“…Both fruits are similar in appearance and shape. It was determined that the pomological values obtained here are quite similar to the values reported in the literature (Kremer, Grubesic, Popovic, & Karlovic, 2012).…”
Section: Pomological Resultssupporting
confidence: 89%
“…Some studies have reported on the inter-and intraspecific variability in the fruit and/or seed traits in the Berberis genus [18][19][20][21][22]. These studies have suggested that the differences between the populations for all the analyzed fruit and seed traits depend on environmental factors and species-related differences.…”
Section: Introductionmentioning
confidence: 99%